CURRENT CONTROVERSIES AND APPROACHES TOWARDS DENTAL AGE ESTIMATION IN FORENSIC CASES - Feodor Odzhakov (Science & Research)

(untitled)
Introduction: Personal identification and age estimation in forensic medical practice are some of the challenging tasks for every expert in the field. Given the undergoing legal investigation, it is important for the most precise conclusions to be drawn. Materials and Methods: For the period 01.01.2015 – 08.05.2018 in the Department of Forensic Medicine and Deontology at University Hospital Aleksandrovska – Sofia, 58 autopsies on deceased of unknown identity have been performed. For the purpose of age estimation full dental examinations have been performed and the age of each corpse has been established via Takei’s morphology method. Results: Following the pattern requested by the Takei’s method, all 58 cases’ age has been estimated, with ages varying between 34 and 80+ years. Later, 41 cases have been identified in the course of investigation. In 7 cases the deviation has been within plus (+) 5 years, in 3 cases – minus (-) 5 years, and in the rest 31 cases the deviation has been found to be within more than ± 10 years. Discussion: This study has revealed that the most commonly used method in age estimation has shown certain deviations which are not to be underestimated. A wild range of possible age would consequence in difficulties during the investigation process. Invasive techniques and such relying on special equipment are practically impossible to be applied in everyday practice due to various reasons. Conclusion: A profound study on population must be performed in order for up-to-date information to be gathered that would result in better age estimation and personal identification process prior to performing a DNA-analysis.